2019
DOI: 10.1161/atvbaha.118.312261
|View full text |Cite|
|
Sign up to set email alerts
|

Apolipoprotein E4 Expression Causes Gain of Toxic Function in Isogenic Human Induced Pluripotent Stem Cell-Derived Endothelial Cells

Abstract: Objective: The ApoE (apolipoprotein) allele epsilon 4 is a major genetic risk factor for Alzheimer disease, cardiovascular disorders, and stroke, indicating that it significantly impacts cerebral and vascular systems. However, very little is known about how APOE genotype affects brain endothelial cells, which form a network of tight junctions to regulate communication between the brain and circulating blood factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 71 publications
1
21
0
1
Order By: Relevance
“…Relative to those of European and Asian descent, individuals of African descent may have up to twice the frequency of the E4 allele [ 65 , 66 ••]. APOE4 is also associated with a higher level of proinflammatory cytokines and promotes prothrombotic properties [ 67 ]. Furthermore, in an analysis of > 400,000 individuals, apoE4 isoforms strongly influenced mass levels of Lp(a) with 65% higher Lp(a) levels in APOE4/4 subjects (Fig.…”
Section: Prevalence Of Lp(a) and Population Differences In Ethnic/racmentioning
confidence: 99%
“…Relative to those of European and Asian descent, individuals of African descent may have up to twice the frequency of the E4 allele [ 65 , 66 ••]. APOE4 is also associated with a higher level of proinflammatory cytokines and promotes prothrombotic properties [ 67 ]. Furthermore, in an analysis of > 400,000 individuals, apoE4 isoforms strongly influenced mass levels of Lp(a) with 65% higher Lp(a) levels in APOE4/4 subjects (Fig.…”
Section: Prevalence Of Lp(a) and Population Differences In Ethnic/racmentioning
confidence: 99%
“…5 Evidence from human induced pluripotent stem cell-derived endothelial cells harboring different APOE genotypes suggests endothelial cells themselves contribute to vascular dysfunction in APOE4 carriers. 6 Other pathways beyond MMP9 can also contribute. Robo4-paxillin-ARF6 signaling in endothelial cells has recently been identified as a key pathway for maintaining vascular integrity.…”
mentioning
confidence: 99%
“…To test the toxicity of a compound, the conventional approach is to apply it directly to a monolayer culture of target cells. Although they lack the sophisticated tissue architecture or biophysical stimulation (e.g., shear stress) present in vivo, numerous studies have demonstrated that iPSC-ECs or iPSC-SMCs cultured in monolayers respond to chemical or genetic stress in ways that are largely consistent with clinical observations or data from primary cells (Zhang et al, 2011;Cheung et al, 2012;Biel et al, 2015;Belair et al, 2016;Tang et al, 2017;Rieker et al, 2019;Chu et al, 2020). For instance, our lab recently found that e-cigarette liquid (e-liquid) triggered a broad array of molecular and functional disorders in iPSC-ECs, including activation of cell apoptosis, increased reactive oxygen species (ROS) production and LDL uptake, as well as reduced cell migration (Lee et al, 2019).…”
Section: D Culture Modelmentioning
confidence: 89%